Religious conflict and regional autonomy in church establishment and Islamic clothing in West Pasaman and Dharmasraya West Sumatera - Nunu Burhanuddin; Ahmad Ali Nurdin; Muhammad Irfan Helmy (IAIN Salatiga, 2019)
This paper analyses how religious minorities in West Pasaman and Dharmasraya have been disturbed by the implementation of regional autonomy policies. By examining the church establishment and Islamic clothing enactment in the region as case studies, the paper shows that the conflicts between Muslims and Christians were caused by the discriminatory regional regulations against minority groups. This study uses an ethnographic approach, consisting of interviews and extensive observational research in the research site to collect the data. The article argues that the implementation of local government policies such as the very strict requirement to establish church and Islamic clothing regulations for students have negative impacts on the harmonious relationship between Muslims and non-Muslims in the region. Thus, local government officers should take into consideration minority and majority-group relationships in creating regional religious regulations.Penelitian ini menganalisa bagaimana kaum minoritas agama di Pasaman Barat dan Dharmasraya terusik dengan implementasi kebijakan otonomi daerah. Dengan mengkaji aturan pendirian gereja dan busana Islami sebagai kasusnya, artikel ini menunjukkan bahwa konflik yang terjadi antara Muslim dan Kristen di daerah tersebut disebabkan karena regulasi otonomi daerah yang bersipat diskriminatif bagi kalangan kaum minoritas. Studi ini menggunakan metode etnografi dengan menggunakan wawancara dan observasi yang ekstensif di lokasi penelitian sebagai teknik pengumpulan data. Peneliti berargumen bahwa penerapan kebijakan pemerintahan lokal seperti ketatnya persyaratan membangun rumah ibadah (gereja) dan aturan kewajiban memakai busana Islam bagi pelajar mempunyai implikasi negatif terhadap hubungan antara Muslim dan non-Muslim di daerah tersebut. Karenanya, pemerintah daerah harus berhati hati dan mempertimbangkan hubungan kelompok minoritas-mayoritas dalam membuat aturan daerah yang berhubungan dengan agama.